Pengaruh Diabetes Self-Management Education Terhadap Kualitas Hidup Penderita Diabetes Melitus Tipe 2 - Dana Prayoga Irawan; Muryani; Anida (Politeknik Karya Husada, 2025)
Background: Type 2 diabetes mellitus is a chronic disease that requires continuous self-management. Poor disease management may negatively affect patients’ quality of life. Diabetes Self-Management Education (DSME) is an educational intervention designed to improve patients’ ability to manage their condition independently. This study aimed to examine the effect of DSME on the quality of life of patients with type 2 diabetes mellitus. Methods: This study used a quasi-experimental design with a one-group pretest–posttest approach. A total of 15 patients with type 2 diabetes mellitus were recruited using purposive sampling. Quality of life was measured using the Diabetes Quality of Life questionnaire before and after the intervention. The DSME program was delivered in groups through six sessions covering the basic concept of diabetes, symptom management, physical activity, dietary management, medication use, access to health services, and program evaluation. Data were analyzed using the Wilcoxon signed-rank test. Results: The findings showed an improvement in quality-of-life scores after the DSME program. The Wilcoxon signed-rank test indicated a significant difference in quality of life before and after the intervention, with a p-value of 0.002. Conclusion: The DSME program improved the quality of life of patients with type 2 diabetes mellitus. DSME may be considered an educational intervention in community nursing and primary care settings.